The - Vale, Lawrence J. (Oxford University Press, 2005)
In 1871, the city of Chicago was almost entirely destroyed by what became known as The Great Fire. Thirty-five years later, San Francisco lay in smoldering ruins after the catastrophic earthquake of 1906. Or consider the case of the Jerusalem, the greatest site of physical destruction and renewal in history, which, over three millennia, has suffered wars, earthquakes, fires, twenty sieges, eighteen reconstructions, and at least eleven transitions from one religious faith to another. Yet this ancient city has regenerated itself time and again, and still endures...